Migration effects on municipalities' expenditures - Matti Viren (Aboa Centre for Economics (ACE), 2016)
In this paper we examine how Finnish municipalities' expenditures depend on the demographic structure of the population. More precisely, we scrutinize the role of foreign citizens: how does the share of foreign citizens out of the total population manifest itself in total expenditures and some key expenditure categories. The study makes use of Finnish panel data from 249 municipalities for the period 2000-2014. Empirical analyses show that foreign population tends to increase per capita expenditures up to the point where the respective semi-elasticity is about one. The result seems robust in terms of different control variables, subsamples of the data and different estimation techniques. Also, it is found that similarly, the unemployment rate of foreign citizens tends to increase municipalities' expenditures.
Keywords: H72; J15; 330; government expenditures; local public finance; migration